Obligation de reclassement et obligation de sécurité : quelle articulation en matière de santé au travail ? - Isabelle Desbarats (Perspectives Interdisciplinaires sur le Travail et la Santé)
In a context marked by increasing concern to protect the health of workers as well as their employment, it is observed that two employers’ obligations—safety and reclassification—play, in French law, a major role in the construction of a right to safety in the workplace and a right to employment. Actually, a comparison of these two obligations seems hazardous, because their field and logic appear to be different. However, such a connection is not only possible, but probably beneficial : possible first, because these two obligations both involve a restriction of the employers’ management power, and also beneficial because everything leads to the belief that the obligation of reclassification can—and even must—be considered as an extension of the obligation of safety.